Prediction of stemless humeral implant micromotion during upper limb activities. (July 2016) - Favre, Philippe; Henderson, Adam D.
Abstract: Background: Adequate primary stability is essential for the long term success of uncemented stemless shoulder implants. The goal of this study was to evaluate the micromotion of a stemless humeral implant during various upper limb activities. Methods: A finite element model was validated by reproducing experimental primary stability testing. Loading from an instrumented prosthesis representing a set of 29 upper limb activities were applied within the validated FE model. Peak micromotion and percentage area for different micromotion thresholds were considered. Findings: In all simulated activities, at least 99% of the implant surface experienced micromotion below 150 μm. Micromotion depended strongly on loading with large discrepancies between upper limb activities. Carrying no external weight and keeping the arm at lower angles induced lower micromotion. Activities representative of demanding manual labor generally led to higher micromotion. Axilla crutches led to lower micromotion than forearm crutches. Micromotion increased when a wheelchair was used on slopes above 2% inclination. Interpretation: Micromotions below the 150 μm threshold below which bone ingrowth occurs were measured over at least 99% of the implant surface for all simulated activities. Peak micromotion dependence on activity type demonstrates the need to consider physiologic in vivo loading and the full contact interface in primary stability evaluations. Focusing on activities with no hand weight and low arm motions during the rehabilitation period may enhance primary stability. For patients unable to walk without aids, axilla crutches and motorized wheelchairs might be more beneficial than forearm crutches and manual drive wheelchairs respectively. Highlights: This is the first finite element study on primary stability of stemless implants. Loading simulating 29 upper limb activities was applied on a validated model. Micromotion above 150 μm never exceeded 1% of the implant–bone interface. There was a strong influence of load and upper limb activities on micromotion. Guidelines are proposed on rehabilitation activities.